Mitochondrial DNA analysis of the putative skeletal remains of Sieur de Marle: Genetic support for anthropological assessment of biogeographic ancestry. (March 2021) - Ambers, Angie; Elwick, Kyleen; Cropper, Emily R.; Brandhagen, Michael D.; Jones, Bradford; Durst, Jeffrey; Gilmore, Kathleen K.; Bruseth, James E.; Gill-King, Harrell
Highlights: In 1932, seven burials were discovered on a Texas plantation (a former Caddo Indian village). One set of skeletal remains (an adult male) was buried in a manner inconsistent with Caddo tradition. Cranial measurements and dietary isotope data support European ancestry for this adult male. Mitochondrial DNA sequencing revealed Haplogroup H or R (further support of European descent). Historical records suggest this may be a member of the French explorer La Salle's last expedition. Abstract: In 1932, seven burials were discovered on a Texas plantation that was originally the site of a 17th-century Caddo Indian village. Of the seven excavated graves, one set of remains (an adult male) was notably buried in a manner inconsistent with traditional Caddoan burial practices and has long been purported to be the remains of Sieur de Marle (a member of the French explorer La Salle's last expedition). Diary accounts of La Salle's expedition scribe report that Sieur de Marle died along a river near an Indian village during a trek to Canada to find help for colonists left behind at the ill-fated Fort St. Louis. Additionally, two lead projectiles recovered from the grave were ballistically analyzed and determined to be consistent with ammunition used in 17th-century weaponry. In the 1980s, anthropologists requested access to the remains for study, but the skull was missing. Cranial measurements recorded in 1940 and 1962 (by two independent anthropologists) were used to investigate the ancestry of this individual; and the Giles-Elliot (G-E) discriminant function was calculated to be 18.1, within the Anglo-European range. Dietary isotope testing on non-cranial skeletal elements determined that this unknown male's diet was rich in animal/marine protein sources, which differs appreciably from Caddo Indian populations of that time period. In order to genetically assess this individual's biogeographic ancestry and to provide further support that this individual is of European descent, mitochondrial DNA (mtDNA) sequencing was performed using the Applied Biosystems™ Precision ID mtDNA Whole Genome Panel. mtDNA sequencing of multiple sections from two different long bones yielded compiled results consistent with either Haplogroup H or R, both predominantly European mtDNA haplogroups. Further anthropological calculations were conducted using cranial measurements, FORDISC™ software, and discriminant function analysis. Two-way, four-way, and multigroup discriminant function analyses further classify this set of unidentified remains as being White (European) in origin, with posterior probabilities of 0.999, 0.881 and 0.986, respectively. Combined with historical records of Sieur de Marle's death, as well as overlays of historical and contemporary maps which demonstrate that the plantation site aligns with Joutel's diary accounts of de Marle's burial, these collective results support that these remains are of a European male and may possibly belong to this prominent member of La Salle's expedition team.